DISEASE PROGRESSION IN PATIENTS WITH LOW-RISK PRIMARY MYELOFIBROSIS – CASE REPORT - Smiljanić, Mihailo; Arsenović, Isidora; Bogdanović, Andrija; Leković, Danijela (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: The median survival (OS) of patients with low-risk PMF is over 15 years, but according to the "MOST" prospective study, disease progression occurs in almost 60% of these patients.Aim: to present the disease course and treatment outcome of patients with low-risk PMF.Case report: All patients were diagnosed with PMF, low-risk IPSS, and normal initial cytogenetics.Case 1: A 61-year-old male patient was admitted in May 2016 with Tr 772x109/L, LDH 566 U/L, no splenomegaly, JAK2V617F+. He was initially treated with hydroxyurea (HU) from 2016 to 2020. In 2021, he was introduced to ruxolitinib due to the development of splenomegaly and leukocytosis, with disease progression 18 months later (spleen 26 cm, Plt 20x109/L, 10% blasts in the marrow, complex karyotype: -5, del 7q, mar+). Azacitidine was introduced, but death occurred due to sepsis in October 2022. OS is 66 months.Case 2: A 47-year-old female patient was admitted in July 2011 with Tr 899x109/L, LDH 899 U/L, spleen 15x7 cm, JAk2V617F+, and ASXL+. She was initially treated with HU and has been treated with ruxolitinib since October 2013 due to the progression of splenomegaly (spleen 19.3 cm, LDH 1881 U/L), with subsequent normalization of spleen size, number of Tr, and LDH. The patient is in remission. OS is 126 months.Case 3: A 64-year-old male patient was admitted in May 2012 with Tr 1457x109/L, LDH 631 U/L, borderline splenomegaly, JAk2V617F-, MPL+, SRSF2+, U2AF1+, ASXL1+. He was initially treated with HU (May 2012) and since April 2019 with danazol due to the emergence of transfusion dependence. Due to heart failure, death occurred in February 2020. OS is 96 months.Conclusion: Some patients with low-risk PMF have disease progression, and future studies will show whether early NGS analysis of non-driver mutations and early initiation of therapy contribute to changing the course of the disease.
Keywords: myeloproliferative neoplasm; primary myelofibrosis; prognosis